Functional Oxide Nanomaterials and Nanocomposites for the Removal of Heavy Metals and Dyes - Sarika Singh; K. C. Barick; D. Bahadur (Nanomaterials and Nanotechnology)
Water scarcity and its contamination with toxic metal ions and organic dyes represent a serious worldwide problem in the 21st century. A wide range of conventional approaches have been used to remove these contaminants from waste. Recently, nanotechnology has been given great scope for the fabrication of desirable nanomaterials with large surface-to-volume ratios and unique surface functionalities to treat these pollutants. Amongst these, oxide-based nanomaterials emerge as promising new materials for water purication. In this review article, we explore a broad-spectrum overview of recent developments in the area of oxide-based nanomaterials, such as Fe3O4, ZnO and TiO2, as well as their binary and ternary nanocomposites, for the removal of various toxic metal ions and organic dyes. The possible adsorption mechanism and the surface modification of adsorbents for the removal of heavy metal ions and dyes are discussed in detail. The sorption properties of the different adsorbents depend on the surface functionalization of nanomaterials, the pH of the medium, and the reaction time and concentration, etc. In addition, we provide a short overview on the study of the selective adsorbents in multi-component sorption systems, along with the future prospects of oxide nanomaterials in water purification.